Achieving legal comparative advertising : a comparative analysis of comparative advertising law in the European Union and Türkiye - Koç Yalın, Meryem (My University, 2025)
Türkiye ile Avrupa Birliği arasındaki ilişkide gümrük birliği ve üyelik sürecinin en önemli aşamalarından biri, Türk Hukuku’nun acquis communautaire olarak adlandırılan Avrupa Birliği müktesebatıyla uyumlu hale getirilmesidir. Bu bağlamda, geçtiğimiz 20 yıl içerisinde Türkiye'de hukukun çeşitli alanlanlarında, Avrupa Birliği mevzuatına paralel düzenlemeler yapılmış olup, Reklam Hukuku müktesebata uyumlanan alanlardan biridir. Bu çalışmanın odak noktası, Türk Hukukunda Ticari Reklam ve Haksız Ticari Uygulamalar Yönetmeliği olup karşılaştırmalı reklamların hukuka uygunluk şartları; Avrupa Birliği’nde Reklam Hukukunun ana kaynağı olan 2006/ 114/ EC Sayılı Reklam Direktifi’nde yer alan hukuka uygunluk koşulları ile mukayeseli şekilde ele alınmıştır. Çalışmanın ilk bölümünde reklam ve karşılaştırmalı reklam kavramları incelenmiş, ikinci bölümde ise Türk Hukukunda ve Avrupa Birliği Hukukunda karşılaştırmalı reklamlara ilişkin düzenlemeler ve reklam denetim mekanizmaları analiz edilmiştir. Son bölümde, Avrupa Birliği’nde ve Türkiye'de reklamları denetleyici idari kurumlar ile yargı mercilerinin karşılaştırmalı reklam hukukuna ilişkin kararları örnek bir yaklaşımla sunulmuş ve söz konusu denetim mekanizmalarının, karşılaştırmalı reklam kurumuna yaklaşımı analiz edilmiştir. Bu çalışmanın amacı, özellikle içtihatlara odaklanarak, Avrupa Birliği ve Türkiye'deki karşılaştırmalı reklamlar ile ilgili yasal düzenlemeler arasındaki benzerlik ve farklılıkları analiz ve karşılaştırma yoluyla gözler önüne sermektir.

One of the most important stages of the customs union and membership process in the relations between Türkiye and the European Union is the harmonization of Turkish Law with the European Union acquis, called acquis communautaire. In this context, in the last 20 years, changes have been made in various areas of law in Türkiye in parallel with the European Union regulations, and Advertising Law is one of these areas. The focus of this study is the Commercial Advertising and Unfair Commercial Practices Regulation in Turkish Law, and the legality conditions of comparative advertising are discussed in a comparative method with the legality conditions in the Advertising Directive No. 2006/ 114/ EC, which is the main source of Advertising Law in the EU. In the first part of the study, the concepts of advertising and comparative advertising are examined, and in the second part, the regulations and advertising control mechanisms regarding comparative advertising in Turkish and European Union Law are analyzed. In the last section, the decisions of the administrative institutions and judicial authorities that control advertisements in the European Union and Türkiye regarding comparative advertising law are presented with an exemplary approach and the approach of the said control mechanisms to the institution of comparative advertising is analyzed. The aim of this study is to reveal the similarities and differences between the legal regulations regarding comparative advertisements in the European Union and Türkiye, focusing especially on the case laws, through analysis and comparison.
Keywords: 2006/ 114/ EC sayılı AB Yönergesi; Advertising; Advertising Law; Advertising laws; Advertising Supervision Mechanisms; Aldatıcı reklam; Avrupa Birliği; Comparative Advertising; Deceptive advertising; EU Directive 2006/ 114/ EC; European Union; Karşılaştırmalı Reklam; Reklam; Reklam Denetim Mekanizmaları; Reklam hukuku; Standards; Standartlar; Turkish Advertising Law; Türk Reklam Hukuku